2020
DOI: 10.1177/1073191120961833
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Bias in the Diagnosis of Borderline Personality Disorder Among Lesbian, Gay, and Bisexual Patients?

Abstract: High prevalence of borderline personality disorder (BPD) diagnosis is observed among sexual minority samples. It is unclear if sexual minority individuals are systematically diagnosed with BPD at higher rates than heterosexual individuals, and if potential diagnostic disparity can be explained by differences in maladaptive personality domains. Utilizing data from partial hospital patients ( N = 1,099) the current study explored (a) differences in the frequency of diagnosis of BPD based on sexual orientation, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 86 publications
2
61
0
Order By: Relevance
“…Despite high prevalence of BPD diagnosis among sexual minority psychiatric samples (Grant et al, 2011;Reuter et al, 2016), and evidence demonstrating provider bias in the provision of the BPD diagnosis based on sexual minority status (Eubanks-Carter & Goldfried, 2006;Rodriguez-Seijas et al, 2020), these results suggest that the majority of BPD criteria do not demonstrate bias at the population level. That is, higher criterion endorsement reflects elevations in transdiagnostic psychopathology experienced by sexual minority individuals rather than item-specific issues independent of psychopathology.…”
Section: Bias In the Diagnosis Of Bpd Among Sexual Minority Individualsmentioning
confidence: 60%
See 2 more Smart Citations
“…Despite high prevalence of BPD diagnosis among sexual minority psychiatric samples (Grant et al, 2011;Reuter et al, 2016), and evidence demonstrating provider bias in the provision of the BPD diagnosis based on sexual minority status (Eubanks-Carter & Goldfried, 2006;Rodriguez-Seijas et al, 2020), these results suggest that the majority of BPD criteria do not demonstrate bias at the population level. That is, higher criterion endorsement reflects elevations in transdiagnostic psychopathology experienced by sexual minority individuals rather than item-specific issues independent of psychopathology.…”
Section: Bias In the Diagnosis Of Bpd Among Sexual Minority Individualsmentioning
confidence: 60%
“…In another study of actual clinical diagnostic patterns, sexual minority patients in a partial hospital setting were more likely to be assigned a BPD diagnosis than heterosexual patients. Importantly, this diagnostic disparity persisted even after transdiagnostic dimensions of personality pathology were controlled (Rodriguez-Seijas et al, 2020). Together, this emerging literature suggests that providers are more likely to assign a diagnosis of BPD to sexual minority individuals than heterosexual individuals, regardless of underlying psychopathology or clinical presentation .…”
Section: Bpd Diagnostic Bias and Sexual Minority Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also revealed that individuals with BPD tend to exhibit homosexual or bisexual orientations (Reich & Zanarini, 2008). Surprisingly, Rodriguez-Seijas et al (2020) found the clinicians bias in the diagnosis of individuals from sexual minority groups, especially bisexual, who were more likely to diagnose BPD. The findings make clear the need to understand individuals from sexual minority groups, whether they actually experience psychopathology such as BPD, or whether their psychopathological symptoms are influenced by their sexual orientation, which is often linked to rejection of a more heterosexual society.…”
mentioning
confidence: 85%
“…Related to appreciating the role context plays in intervention, understanding the social and structural context is also important for assessment and measurement purposes. For instance, emerging research suggests that clinical providers are more inclined to provide diagnoses of more severe forms of psychopathology (e.g., borderline personality disorder) among sexual minorities than heterosexual persons (Eubanks-Carter and Goldfried, 2006;Rodriguez-Seijas, Morgan and Zimmerman, 2021b). Relatedly, research using populationbased data further shows that sexual minority persons are more likely to endorse several criteria of severe psychiatric disorders if one does not account for associated distress or impairment related to those criteria.…”
Section: Assessment and Contextmentioning
confidence: 99%